Casedrip / Muhammad Faris Zakwan Hamka and Aeman A Malik - Hamka, Muhammad Faris Zakwan; A Malik, Aeman (2022)
Casedrip is one of the casing brands which was created to protect the smartphone from scratches or any defects. At Casedrip, we have a variety of designs that are sure to appeal to all smartphone users. For those who are interested in the hype beast, or the ordinary but beautiful, this is the place to buy a casing for your favorite smartphone. Practically all societies in the world use smartphones. Therefore, the target customer for Casedrip is for all smartphone users throughout Malaysia and if given sustenance, it is possible to reach abroad. Casedrip started running the business from April 22, 2022. Starting with the design checkers that have raised the name of Casedrip, from there began the legacy of Casedrip until now which has more than 10 designs. Last but not least, we are using Facebook as our main social media to reach to our market. Facebook is a great platform to make engagement to the market and compete in the era of industry 4.0 that using a connected devices and manage big data is a priority. Our product will get more attention when we drop some discount or combo by 3 free one. A lot of customer love to buy the product that have discount. So that, they can buy a lot of our products.